The Role of Teachers in Implementing Local Wisdom-Based Learning in Elementary Schools in Makassar - Dyan Paramitha Darmayanti; Nurlela; Salwia; Darman Manda (Universitas Sulawesi Barat, 2026)
Basic education plays a crucial role in shaping students’ character and cultural identity, including through learning based on local wisdom. In this context, teachers occupy a central position as agents who bridge the curriculum with the cultural values that thrive in students’ communities. This study aims to examine the role of teachers in implementing local wisdom-based learning in elementary schools in Makassar City, covering teachers’ understanding of local wisdom, the forms of integration in learning, the challenges they face, and the impact on students. The study employs a qualitative case study design at SD Muhammadiyah Perumnas and UPT SPF SD Inpres Cilallang. Data were collected through in-depth interviews with teachers and school principals, classroom observations, and analysis of learning documents, and were analyzed using thematic analysis with triangulation of sources and techniques to ensure data validity. The research findings indicate that teachers at both schools possess a fairly good understanding of Bugis–Makassar cultural values such as tabe', Siri' na Pacce, and gotong royong, and actively integrate them into various subjects such as Pancasila Education, Civic Education, and Cultural Arts, through an integrative thematic and values-based approach. The forms of integration implemented by teachers include teaching the traditional Mappadendang dance, folk tales, the use of the local language, and instilling the value of tabe' in daily interactions. In carrying out their roles, teachers face three main challenges: limited resources and facilities, low parental support, and the absence of clear policy guidelines. Nevertheless, teachers' role in local wisdom-based learning has a positive impact, evidenced by increased student politeness and a growing sense of pride in local culture. This study concludes that optimizing teachers' roles requires a harmonious educational ecosystem encompassing schools, families, and policy.